2014
DOI: 10.1371/journal.pone.0088970
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Development of Cervical Spine Instabilities in Rheumatoid Arthritis: A Prospective Minimum 5-Year Cohort Study

Abstract: ObjectiveTo clarify the incidence and predictive risk factors of cervical spine instabilities which may induce compression myelopathy in patients with rheumatoid arthritis (RA).MethodsThree types of cervical spine instability were radiographically categorized into “moderate” and “severe” based on atlantoaxial subluxation (AAS: atlantodental interval >3 mm versus ≥10 mm), vertical subluxation (VS: Ranawat value <13 mm versus ≤10 mm), and subaxial subluxation (SAS: irreducible translation ≥2 mm versus ≥4 mm or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 48 publications
3
40
1
3
Order By: Relevance
“…The prevalence of cervical spine involvement has been shown to range from 16% to 70.4%, and AAS has been reported to be the most common abnormal finding1424). The risk factors for cervical involvement have been shown to be peripheral hand or foot joint erosion1424), disease-modifying antirheumatic drug (DMARD) failure4), corticosteroid use24), and age at RA diagnosis1). Additionally, our study found that the CRP level and time interval between RA diagnosis and radiographic hand joint erosion were risk factors for surgically treated AAS development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of cervical spine involvement has been shown to range from 16% to 70.4%, and AAS has been reported to be the most common abnormal finding1424). The risk factors for cervical involvement have been shown to be peripheral hand or foot joint erosion1424), disease-modifying antirheumatic drug (DMARD) failure4), corticosteroid use24), and age at RA diagnosis1). Additionally, our study found that the CRP level and time interval between RA diagnosis and radiographic hand joint erosion were risk factors for surgically treated AAS development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that radiographic hand and foot joint erosion in radiographs was the most common risk factor for cervical involvement in RA patients141024). Proliferative and erosive synovitis progresses to destruction of the articular cartilage, especially in metatarsophalangeal joints, which are the most commonly involved joints10), and the cervical spine is the second most commonly involved region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations